Quantifying the Evolution of Vascular Barrier Disruption in Advanced Atherosclerosis with Semipermeant Nanoparticle Contrast Agents - Zhang, Huiying (Public Library of Science, 2011)
RATIONALE: Acute atherothrombotic occlusion in heart attack and stroke implies disruption of the vascular endothelial barrier that exposes a highly procoagulant intimal milieu. However, the evolution, severity, and pathophysiological consequences of vascular barrier damage in atherosclerotic plaque remain unknown, in part because quantifiable methods and experimental models are lacking for its in vivo assessment. OBJECTIVE: To develop quantitative nondestructive methodologies and models for detecting vascular barrier disruption in advanced plaques. METHODS AND RESULTS: Sustained hypercholesterolemia in New Zealand White (NZW) rabbits for >7–14 months engendered endothelial barrier disruption that was evident from massive and rapid passive penetration and intimal trapping of perfluorocarbon-core nanoparticles (PFC-NP: ∼250 nm diameter) after in vivo circulation for as little as 1 hour. Only older plaques (>7 mo), but not younger plaques (<3 mo) demonstrated the marked enhancement of endothelial permeability to these particles. Electron microscopy revealed a complex of subintimal spongiform channels associated with endothelial apoptosis, superficial erosions, and surface-penetrating cholesterol crystals. Fluorine ((19)F) magnetic resonance imaging and spectroscopy (MRI/MRS) enabled absolute quantification (in nanoMolar) of the passive permeation of PFC-NP into the disrupted vascular lesions by sensing the unique spectral signatures from the fluorine core of plaque-bound PFC-NP. CONCLUSIONS: The application of semipermeant nanoparticles reveals the presence of profound barrier disruption in later stage plaques and focuses attention on the disrupted endothelium as a potential contributor to plaque vulnerability. The response to sustained high cholesterol levels yields a progressive deterioration of the vascular barrier that can be quantified with fluorine MRI/MRS of passively permeable nanostructures. The possibility of plaque classification based on the metric of endothelial permeability to nanoparticles is suggested.